Diffusion in advanced materials - Murch, G. E.; Öchsner, Andreas; Belova, Irina (Diffusion foundations ;, 2014)
In the first chapter Prof. Kozubski and colleagues present atomisticsimulations of superstructure transformations of intermetallic nanolayers. In Chapter 2, Prof. Danielewski and colleagues discuss a formalism for themorphology of the diffusion zone in ternary alloys. In Chapter 3, ProfessorsSprengel and Koiwa discuss the classical contributions of Boltzmann andMatano for the analysis of concentration-dependent diffusion. This isfollowed by Chapter 4 by Professor Cserháti and colleagues on the use of Kirkendall porosity for fabricating hollow hemispheres. In Chapter 5,Professor Morton-Blake rep.